MACROECONOMICS EFFECT ON CONVENTIONAL AND SHARIA STOCKS DURING THE COVID-19 PANDEMIC - Halisa, Novia Nour; Annisa, Selvi (IJIBE (International Journal of Islamic Business Ethics), 2022)
This study aims to analyze the effect of macroeconomics on conventional and sharia stocks during the COVID-19 pandemic. The data collected for this study was obtained from monthly stock index data on the Indonesia Stock Exchange (IDX) as well as macroeconomic development reports from the Ministry of National Development Planning/Bappenas. The population in this study are all conventional and sharia stocks listed on the IDX. The sampling technique was carried out using a purposive sampling method with the criteria of conventional and sharia stocks listed on the IDX for the period March 2020 to June 2021. The macro variables used in researching the Jakarta Composite Index (JCI) and the Jakarta Islamic Index (JII) consisted of four variables, which are exports, imports, inflation rate, and foreign exchange reserves. The data analysis technique used in this research is multivariate multiple linear regression analysis accompanied by simultaneous and partial testing to determine the predictor variables that affect JCI and JII. The results shows that exports and foreign exchange reserves had a significant positive effect on JCI and JII, while imports and the inflation rate did not have a significant effect. The goodness of the model is 93%.